English language teaching through student-centered activities: An overview - R. B, Dhivya.; M, Ilankumaran (Edelweiss Applied Science and Technology, 2024)
Student-centered activities in teaching English transform the traditional role of teachers and learners in the classroom. This method moves the emphasis from the instructor as the exclusive authority to the students as active contributors to their own education. In this paper, the roles of teachers and learners in student-centered activities of teaching English, highlighting their responsibilities and contributions to creating a dynamic and active learning environment have been explored. It takes a dynamic, inclusive approach to teach English to multiple students, taking into account their varied backgrounds, requirements, and skill levels. This paper also projects effective strategies and approaches for teaching English to multilevel students, seeking to establish a welcoming classroom that accommodates each student's unique requirements. With these strategies and approaches, teachers can effectively nurture the language skills of multilevel students, equipping them with the tools for successful communication and fostering their growth as global citizens. Teaching English to multilevel students presents a host of challenges that educators must navigate effectively. By embracing certain roles, teachers and learners forge a partnership that empowers learners and cultivates a lifelong love for learning English. As a whole, the benefits and strategies of teaching English through student-centered activities, emphasizing the importance of empowering students and promoting meaningful language acquisition have also been discussed in detail.